PERSEPSI GURU PENGETAHUAN ALAIWBIOLOGI SMPN DI KECAMATAN SUKOHARIO TERIIADAP KURIKULUM 2OO4 (STUDI KASUS DI KABUPATEN SUKOHARJO) - E. SUSIOWATI, SRI MULYANI (BIOEDUKASI, 2006)
AbstractThe Curriculum of 2004 can be succesfully conducted if teachers have a correct perception on it. So,this research concerning on the perception of the teachers of biological subject upon the curriculum. Theperception it self was interpreted in a view point of organization, and the interpretation toward the curriculum.23 teachers on biology were used as sample which were taken from the population of teachers onbiology of Sukoharjo district (belongs to 7 junior high schools. The data were collected by using checklist,interview and documentation. Two form of checklist carried out were the attitude scales and the knowledge.The data obtained were then analyzed descriptively in a percentage.The result of this research indicate that the attitude of teachers on biology to the Curiculum of 2004were in the medium scale, beside the knowledge about the curriculum were in the good scaleKeywords: Perception toward the curiculum of 2004, teachers in biology